GROWTH, DEVELOPMENT AND YIELD OF SWEET CORN DEPENDING ON THE TYPES OF BASIC TILLAGE - Masliiov, S. V.; Masliiov, Y. S.; Tsygankova, N. A.; Rudakov, V. S. (Scientific Progress & Innovations, 2020)
The most important problem of modern agricultural production is the study and implementation of effec-tive tillage methods. They protect soil from wind and water erosion, optimize soil living conditions of plants, increase fertility and provide the formation of stable high-quality crops. It especially concerns the Steppe zone of Ukraine where Luhansk region is located. The purpose of our research was to examine the main types of tillage, substantiate recommendations for improving the elements of technology in cultivating such row crop as sweet corn. The influence of basic and pre-sowing tillage on the formation of sweet corn yield was studied in field experiments conducted from 2017 to 2019. We considered the main types of tillage such as plowing to a depth of 20–22 cm, subsurface soil cultivation to a depth of 20–22 cm and shallow tillage with a disc cultivator at 10–12 cm. These tillage techniques make the soil fine, increase nutrient cycle, re-duce weeds and cover fertilizers and crop residues to the required depth. Consequently such measures help to create conditions for receiving good harvest of sweet corn in future. Plowing at 20–22 cm in combination with several pre-sowing cultivations ensured the formation of the maximum yield. During the wet years the yield of sweet corn ears reached10.0-12.0 t/ha and during the arid years it was 6.50-7.00 t/ha. Subsurface tillage to the same depth did not give positive results. The yield of sweet corn was 6.58-9.62 t/ha on average or 0.66–0.95 t/ha less than at plowing. When carrying out shallow tillage 10–12 cm deep, the yield of sweet corn ears was even less – 6.11–8.99 t/ha. The highest yield of sweet corn ears was obtained at plowing and three pre-sowing soil cultivations. Replacing plowing with subsurface loosening or fine tillage and reducing the number of pre-sowing soil cultivations from three to one led to a reduction in the yield of sweet corn ears.